Meningioma in pregnancy and perinatal outcomes - Astrit M. Gashi; Jakup Ismajli; Curr Gjocaj; Atdhe Keqa; Visare Batalli; Qefsere Mulaj (Romanian Journal of Neurology, 2018)
A pregnancy is categorized as with high-risk when the mother is diagnosed with any tumor in the brain. Meningiomas are tumors that take origin from the arachnoid villi and produce a globoid or discoid mass. Meningiomas account for approximately 38 percent of all intracranial tumors in females and 20 percent in males. They are usually localized in parasagittal areas, convexities of the cerebral hemispheres, the olfactory groove, and the lateral wing of the sphenoid. Most meningiomas are diagnosed in women between 30 and 50 years old. For meningiomas diagnosis are used: MRI, CT, and very rarely angiography. Tumors in the brain can be typical or benign, atypical, anaplastic or malignant. 88-94% of meningiomas are benign tumors. During pregnancy, MRI is most recommended for the diagnosis and evaluation of brain meningiomas. We report the management of a 26-year-old woman patient diagnosed with olfactory groove meningioma, who has been subjected to one bifrontal craniotomy and gross total resection (GTR) (Simpson grades I/II), on week 33 of gestation, without any complications as during surgery that lasted 6 hours, as well as during pregnancy and childbirth.